Enhancement of Zakat distribution management system : case study in Lembaga Zakat Selangor / Nurin Sofiya Mohamad Nadzli. - Mohamad Nadzli, Nurin Sofiya (2019)
Zakat can be approached to encounter social problem such as poverty in society by sharing the percentage of wealth to relevant recipients as the obligation to the person who affordable. According to the role of Lembaga Zakat Selangor (LZS) in distributing zakat to asnaf in Selangor, this study attempts to investigate the ways to enhance zakat distribution management system to develop the effective zakat distribution process. This research had been conducted by qualitative method such as interview session to collect the data and answer this research purpose. The interview session had been participate by Encik Khairul Azhan Bin Ahmat, Head of Zakat Distribution Department of Research Division and Center of Excellence, Abdul Razak bin Razali, Head of Gombak Regional Distribution Operations and Gombak Regional Distribution Operations Executives who are Mohammad Noor Afiq Bin Mohamad Isnan, Mohd Sabhi Bin Mohamad Misran and Hj Ramli . After the data collection process was done, it had been analysed and the result had been recorded systematically. From the data that had been analyse, a lot of enhancement of zakat distribution management system can be found.